Game Perang Kemerdekaan di Pulau Jawa - Ferry Hartanto; Kristo Radion Purba; Leo Willyanto Santoso (Jurnal Infra, 2017)
Lately many younger generation that lazy, doesn’t care and doesn’t want to learn about history, they think history is not important. Actually history is a important knowledge because it can give a country unique identifier that make a country different from another country because there is no two country with exact same history and background so history can make a country different from the other.A game will be made to teach history to younger generation. Game will have adventure-strategy genre. In strategy section player will view story and answer given question and choose from the given choice. In strategy section player will play Turn-Based strategy they will play in order with the enemy once at a time.From the test and survey it can be determine that the game is working smoothly and all function has been work there is no error function. There is advice to improve the design.